UJI PEMBERIAN JENIS KOMPOS TERHADAP PERTUMBUHAN BIBIT KOPI ARABIKA (Coffea arabica L.) - Valty E.H. S; wardati wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The use of several kinds of compost on the arabica coffee seedlingis an effort to provide organic fertilizer from agricultural waste.This fertilizer is espected to improvethe growth of coffee seedling, because it has function as the source of nutrient and it is able to improve the physical and biological properties of soil. The research was carried out on the experimental station, Faculty of Agriculture, University of Riau on December 2016 – March 2017, by using a completely randomized design with the treatment without compost, cocoa fruit skin compost, OPEFB compost, tofu compost, straw compost, legume compost with dosage100 g/polybag. The growth observed was seedling height, stem diameter, number and area of leaves, root volume, root-shoot ratio, and dry weight of seedling.The result showed that giving ofseveral kinds of composteffect on parameter of area of leaves, root-shoot ratio, dry weight of seedling.The best treatment was obtained of legume compost 100 g/polybaghigher on parameter of seedling height, stem diameter, number and area of leaves, root-shoot ratio and dry weight of seedling.Key word : Arabica coffee seedling (Coffea arabica L.), Compost